A Study of Applications of Rigid Bronchoscopy in Pediatric Patients - Sinha, Vikas (Springer India, 2013)
The aim of the study was to analyse the various indications of rigid bronchoscopy in paediatric patient, the common clinical symptoms, radiological findings, and outcomes of the procedure. A retrospective study was conducted at ENT Department at M. P. Shah Govt Medical College, Jamnagar, and Gujarat, India from 2010 to 2012. Total 50 cases of pediatric age group less than 12 years of age on whom rigid bronchoscopy was performed were included in this study. The diagnosis was based on clinical history, thorough clinical examination and radiological assessment. The total duration of the study was 3 years which included 50 Pediatric cases, males (76 %) were more common as compared to females (24 %), the most common age group which underwent the bronchoscopy was 1–3 years of age. Most common indication for doing rigid bronchoscopy was foreign body aspiration in 84 % of cases (n = 42) followed by other indications like Subglottic stenosis (6 %), Mucous Plugs (4 %) and Bronchoalveolar lavage (4 %). Rigid bronchoscopy has been a saviour and an essential part of standard medical practices for both Therapeutic and Diagnostic purposes. Proper history taking is an cardinal requirement before the procedure, and it is always better to rely on clinical findings rather than radiological findings. It is sensible to perform a Check Bronchoscopy in all cases to revisualise key areas and avoid missing any abnormality or foreign body.